Heidegger, Aristotle and the Work of Art - Sinclair, Mark. author. aut Link
X, 219 p.
Keywords: This book finds Heidegger's Aristotle interpretation integral to his idea of leading metaphysics back to its own presuppositions, and his reflection on art as necessitating a revision of this interpretation. It argues that this tracing is vital to engaging with the historical significance of his thinking, and with modern metaphysics and aesthetics.